The Urgency of Developing Quality Human Resources in Realizing Good Governance: A Literature Review - Alamsyah, Kamal; Irwandi; Komar, Mas Adi; Sujana, Nesan; Ramadhani, Putri; Mustajam, Ajam (Global Writing Academica Researching and Publishing, 2023)
This article discusses the urgency of developing quality human resources in realizing good governance based on a literature review. Good governance is an important goal in effective and just governance. The development of quality human resources has a central role in achieving good governance. Literature review is carried out by reviewing various studies, scientific journals, and literature related to human resource development and good governance. The results of the review show that the development of quality human resources has a significant role in realizing good governance. Effective human resource development practices contribute to transparency, accountability, participation, quality of public services, and integrity in decision making. Skilled, well-trained and competent human resources can improve organizational performance and make a positive contribution to achieving good governance goals.